Gender Equality as a Brand in Icelands Foreign Policy - Karlsdóttir, Kristín Sandra; Ómarsdóttir, Silja Bára (Veftímaritið Stjórnmál og stjórnsýsla, 2020)
This study explores the branding of gender equality in Iceland’s foreign policy. It also attempts to identify the methods used for branding, and the factors leading to the use of gender equality as a brand. The study builds on a broad theoretical base, drawing from small state theories, nation branding, and feminist international relations. The study builds on five in-depth interviews with current and former Foreign Service members in Iceland. Discourse analysis was employed to analyze the data, resulting in three main themes which are explored. These are; gender equality as a brand, methods of branding, and supply and demand. The study finds that branding is conducted sub-consciously, appearing as a rich emphasis on the field throughout the Icelandic Foreign Service, at home and abroad. A more targeted branding is also present when it comes to the engagement of men in the discussion of gender equality. Iceland employs three main methods of branding: Gender equality, agenda setting, and international cooperation. Supply and demand appears to be the main reason for Iceland to choose gender equality as a brand. Iceland has a lot to offer, has taken the lead on the issue and earned the attention of the international community for its efforts. This attention has encouraged the state to continue its work in the field. Nonetheless, the status and the purpose for which it is sought must be scrutinized. Þessi rannsókn greinir hvernig vörumörkun birtist í utanríkisþjónustu Íslands í gegnum jafnréttismál. Einnig er leitast við að greina hvaða aðferðir eru nýttar við vörumörkun og hvaða þættir valda því að jafnréttismál verða fyrir valinu. Breiður kenningarammi er mótaður úr kenningum smáríkjafræða, kenningum um vörumörkun ríkja og femínískum fræðum í alþjóðasamskiptum. Tekin voru viðtöl við fimm fyrrverandi og núverandi starfsmenn utanríkisþjónustu Íslands og orðræðugreiningu beitt á þau. Þrjú þemu voru mótuð út frá niðurstöðum orðræðugreiningarinnar; vörumerkið jafnrétti, aðferðir við vörumörkun og framboð og ...